STRATEGI PEMASARAN PERUSAHAAN BARA TEKNIK YOGYAKARTA - Yunita Fitri Wahyuningtyas; A. Majid Syafi’i; Eka Ambara (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
Competition is very important for the success or failure of a company. Company competition to excel or achieve high performance by implementing strategies, aiming to achieve a profitable and strong position to stem competition in the industry. To determine the marketing strategy of the company Bara Teknik Yogyakarta. This study uses a descriptive qualitative type of research. Research informants in this study were employees of the Yogyakarta Bara Teknik Company as many as 6 people consisting of 2 admins and 4 technicians. In this study, the analysis was carried out by describing the marketing strategy of Bara Teknik Yogyakarta with a SWOT application analysis. The position of Bara Teknik Yogyakarta business sustainability strategy through SWOT and TOWS analysis is in quadrant I. With a strength of 1 and an opportunity of 0.5, it means that Bara Teknik Yogyakarta has strengths and opportunities but is at a low point when multiplied by a scale of 10%, the strength is at 10% and 5% chance so that it requires an alternative strategy for Bara Teknik Yogyakarta medium term SO strategy. Strategies that can be applied include the Strength Opportunities (SO) strategy by maximizing the strengths you have and paying attention to market opportunities. An alternative strategy that can be applied by Bara Teknik Yogyakarta after knowing the marketing position of its business is by utilizing information technology as a means of promotion and expanding market networks and by making marketing designs always updated and following the development of fashion opportunities to compete with competitors.